Dakwah dan Tradisi Pondok Pesantren Salaf: Studi pada Pondok Pesantren Raudhatu Tahfidzil Quran Perak Jombang - Rita Mahfudlotus Zahro; Moh. Abdul Wahab Tsalatsa (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2021)
One of the Islamic educational institutions in Indonesia is Pondok Pesantren, it is the first and oldest education system in Indonesia because the nature of Islam and Indonesians integrate with pesantren is the main attraction, Over time, Islamic boarding schools have developed very rapidly. However, it is possible that there are various obstacles that arise. Islamic boarding school activities are developed through activities that have religious values, such as the commemoration of the great new of Islam, tahfidzul quran, istighosah, manaqib, and reciting the yellow book. That way, these activities serve as a support and complement to the learning in Islamic boarding schools. This study aims to determine how much the preaching and traditions of the Raudhatu Tahfidzil Quran Perak Jombang Islamic boarding school are towards the surrounding community. This type of research uses qualitative research methods with data collection through interviews, observations, and book literature that supports the collected data.